Treinta días en Moscú: the writing of a travel book - Prieto, José Manuel (Caracol, 2012)
"A Month in Moscow" is a travel account focused on the Russian metropolis in the mythic year of 2000. These texts reflect the life of the metropolis, its problems, and its inhabitants. Renowned Cuban novelist, translator and essayist Jose Manuel Prieto arrive in Moscow ar a unique moment in its recent history, when it was going through profound transformations, and had the opportunity to interview the protagonists of these changes.